2019
DOI: 10.3390/cancers11050733
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Evaluation of CA72-4 for Screening Gastric Cancer in a Healthy Population: A Multicenter Retrospective Study

Abstract: Early detection is important for improving the survival rate of patients with gastric cancer (GC). Serum tumor markers have been widely used for detecting GC. However, their clinical values remain controversial. This study aims to investigate the role of serum cancer antigen 72-4 (CA72-4) in the diagnosis of GC in a healthy population. A total of 7757 adults who underwent upper gastrointestinal endoscopy and serum CA72-4 level measurement in multicenters in Taiwan from January 2006 to August 2016 were recruite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 23 publications
1
24
0
Order By: Relevance
“…Although CA724 had a high diagnostic value in GC, its sensitivity was only approximately 45.0% [19]. Moreover, in China, CA724 has been suggested to be associated with Helicobacter pylori infection [21] and even geographical environmental factors, such as temperature [22]. These ndings imply that there might be a bias to evaluate the condition of patients merely depending on CA724.…”
Section: Discussionmentioning
confidence: 99%
“…Although CA724 had a high diagnostic value in GC, its sensitivity was only approximately 45.0% [19]. Moreover, in China, CA724 has been suggested to be associated with Helicobacter pylori infection [21] and even geographical environmental factors, such as temperature [22]. These ndings imply that there might be a bias to evaluate the condition of patients merely depending on CA724.…”
Section: Discussionmentioning
confidence: 99%
“…Although CA724 had a high diagnostic value in GC, its sensitivity was only approximately 45.0% [ 19 ]. Moreover, in China, CA724 has been suggested to be associated with Helicobacter pylori infection [ 21 ] and even geographical environmental factors, such as temperature [ 22 ]. These findings imply that there might be a bias to evaluate the condition of patients merely depending on CA724.…”
Section: Discussionmentioning
confidence: 99%
“…Cancer antigen 72-4 (CA 72-4) is a first-line classical tumor marker with the highest diagnostic sensitivity for GC. Its concentration may also be elevated in patients with colon, pancreatic, breast, or ovarian cancer [ 6 ]. A study performed by Joypaul et al demonstrated that CA 72-4 is a reliable marker in GC and that serial sampling may help to identify recurrence early [ 7 ].…”
Section: Gastric Cancermentioning
confidence: 99%